Altered associative learning and emotional decision making in fibromyalgia - Walteros, César (2011)
Objective: The present study examines the possibility that a chronic pain condition, such as fibromyalgia, was associated with deficits in decision making and associative learning. Methods: Fifteen patients with fibromyalgia (aged 42–59 years) and 15 healthy controls (aged 39–61 years) participated in the experiment. Subjects completed anxiety (STAI) and depression (BDI) questionnaires, as well as standardized neuropsychological tests (Stroop and WAIS subscales). In addition, an emotional decision-making task (Iowa Gambling Task) and a conditional associative learning task (CALT) were administered to all participants. Results: Results indicated that fibromyalgia had a poorer performance than healthy controls in both tasks, showing more perseveration errors in the learning task, and more disadvantageous decisions, as well as a more random behavior in the gambling task. Moreover, we observed that poor performance on the associative learning task was mediated by depression, whereas performance on the gambling task was not influenced by depression. No group differences were found on the standardized neuropsychological tests. Conclusion: These findings indicate that pain and depressive symptoms in fibromyalgia might lead to significant deficits in emotionally charged cognitive tasks. Furthermore, it suggests that chronic pain might impose a high cost on executive control, undermining mainly affective processes involved in learning, memory, attention, and decision-making.